Two-photon photoemission from CoO layers on Ir(1 0 0). (20th January 2016) - Otto, Sebastian; Fauster, Thomas
Abstract: Two-photon photoelectron spectroscopy is used to study the unoccupied electronic states of cobalt oxide layers on Ir(1 0 0). For thicker layers of (1 0 0) orientation the conduction band minimum is found 2 eV above the Fermi level. Layers with (1 1 1) orientation and thickness 4 bilayers show a peak around 3.4 eV energy and no evidence for the conduction band minimum. This is attributed to the metallic character of thin CoO(1 1 1) layers.